Meningkatkan Keterampilan Berpikir Kritis dengan Model PBL Fase D Kelas IX SMP Negeri Linggang Mapan - Niko Yokubus; Andarweni Astuti; Hartutik Hartutik; Sugiyana Sugiyana; Nerita Setiyaningtyas (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to improve the critical thinking skills of ninth-grade students at SMP Negeri 4 Linggang Mapan through the implementation of the Problem-Based Learning (PBL) model in the topic Living in Harmony with Nature. Critical thinking skills are essential in education, especially for developing abilities in analysis, evaluation, and problem-solving. The research method used is Classroom Action Research (CAR), conducted in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. The subjects of this study were ninth-grade students in Phase D, with data collection techniques including observation, tests, and interviews. The results of the study show that the implementation of the PBL model significantly improved students’ critical thinking skills. This is evidenced by an increase in the average score of critical thinking tests from Cycle I to Cycle II, as well as an increase in students' active participation in discussions and problem-solving activities. Based on these findings, it can be concluded that the PBL model is effective in enhancing students’ critical thinking skills. Therefore, it is recommended that educators adopt the PBL model as an alternative teaching approach, particularly for topics that require higher-order thinking skills.